2018
DOI: 10.1108/ajb-10-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Audit fee trends from 2000 to 2014

Abstract: Purpose Setting audit fees is a persistent source of stress for auditors who must, on one hand, comply with the increasing government regulations that generally cause costs to rise; and on the other hand, respond to client pressures to keep audit fees down. In the post-scandal environment of Enron, WorldCom, and the demise of Arthur Andersen, policy makers have introduced additional costs for auditors by increasing regulations and creating a new industry watchdog – the Public Company Accounting Oversight Board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(46 reference statements)
0
3
0
2
Order By: Relevance
“…According to prior research on listed companies, audit client risk is an essential determinant of audit fees since it reflects the nature of the company’s business and the monitoring environment it is subjected to Chan et al (1993). Based on previous international research in this area (Gonthier-Besacier and Schatt, 2007; Naser and Nuseibeh, 2007; Dey and Lim, 2018), audit client risk positively impacted audit fees. Bell et al (2001) found that high business risk increased the number of audit hours.…”
Section: Literature Review and Development Of Research Frameworkmentioning
confidence: 99%
“…According to prior research on listed companies, audit client risk is an essential determinant of audit fees since it reflects the nature of the company’s business and the monitoring environment it is subjected to Chan et al (1993). Based on previous international research in this area (Gonthier-Besacier and Schatt, 2007; Naser and Nuseibeh, 2007; Dey and Lim, 2018), audit client risk positively impacted audit fees. Bell et al (2001) found that high business risk increased the number of audit hours.…”
Section: Literature Review and Development Of Research Frameworkmentioning
confidence: 99%
“…Perusahaan perlu menanggung biaya untuk mengaudit laporan keuangan yang disebut biaya audit (Hendi & Yulinar, 2017). Penetapan biaya audit merupakan hal yang selalu menjadi pertimbangan auditor (Dey & Lim, 2018). Ikatan Akuntan Publik Indonesia (IAPI) menetapkan pedoman pembayaran biaya audit, tetapi pada kenyataannya biaya audit yang dibayar oleh perusahaan berbeda-beda (Wea, 2019).…”
Section: Pendahuluanunclassified
“…Nilai biaya audit dipengaruhi oleh variabel-variabel tertentu. Beberapa penelitian menguji faktor-faktor yang menimbulkan pengaruh terhadap biaya audit, seperti ukuran KAP (Mustapha et al, 2020), effective tax rate, cash tax rate (Onatuyeh & Ukolobi, 2020), rotasi komposisi komite audit (Sellami & Cherif, 2020), dualitas peran CEO (Farooq et al, 2018), pengalaman dewan direksi (Al-Hamadeen et al, 2021), pengalaman komite audit (Drogalas et al, 2020), koneksi politik (Shakhatreh & Alsmadi, 2021), kerumitan audit, risiko audit, karakteristik auditor (Dey & Lim, 2018), dan lainnya. Model penelitian ditunjukkan melalui Gambar 1.…”
Section: Pendahuluanunclassified
“…The municipal audit market was later studied, providing additional insights into determinants of audit fees (Baber, 1983; Baber et al, 1987; Bandyopadhyay & Kao, 2005; Copley, 1989; Rubin, 1988; Ward et al, 1994). Through important meta‐analysis, insight into audit fees was further expanded (Carson et al, 2014; Cobbin, 2002; Dey & Lim, 2018; Hay, 2013; Hay et al, 2006; Vermeer et al, 2009). With the recent growth and evolution of the public sector, there is renewed interest in research looking at the impact of these developments on municipal audit pricing (Collin et al, 2017; Hay & Cordery, 2018, 2021a, 2021b; Lapsley & Miller, 2019; Mattei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%